INVESTIGATING THE ROLE OF EXTERNAL AUDIT ON THE QUALITY OF FINANCIAL REPORTS, COMPANY PERFORMANCE, AND EARNINGS POWER - Murtadha Saleh Mahdi; Mohammed Sadeq Jappar; Ahmed Hassein Machi (Scholar Express Journals, 2023)
This study aims to investigate the effects of external audit quality on the performance of Tehran Stock Exchange companies. The effects of the quality of external auditing on the quality of financial reports have been studied. The effects of profit power on corporate performance were also studied. To present the results of the different models selected in this study, market-based measurement and accounting for corporate performance was used. In order to verify the objectives of the study, three research hypotheses were developed based on 151 companies with a total of 1208 annual company observations from Iran, which were used. This study has shown that the quality of the external auditor and profit power are good governance mechanisms that reduce the agency problem and thus increase corporate performance. In particular, this study finds a positive and significant effect of external auditor quality on firms' performance with respect to accounting and market-based measures. Therefore, this study advises companies to improve the quality of external auditors, because this helps companies increase the stability of their economy in the future. This study also shows the positive and significant impact of the quality of external auditing on the quality of financial reports. Finally, this study showed that there is no relationship between the power of profit and the performance of companies
Keywords: external audit; financial reports; earnings power